Supercritical CO2 flowing upward in a vertical tube subject to axially nonuniform heating - Li, Xin; Sun, Feng; Xie, Gongnan; Boetcher, Sandra K. S. (Numerical heat transfer. Part A, Applications, 2020)
Three different types of axially nonuniform heat fluxes are imposed on the outer surface of a vertical circular tube with turbulent supercritical carbon dioxide (S-CO 2 ) flowing upward. The aim is to explore the potential in adjusting the axial heat flux distribution to optimize heat transfer. Numerical simulations are conducted to investigate how varying the heat flux in the axial direction influences several convective heat transfer behaviors (DHT: deteriorated heat transfer, NHT: normal heat transfer, EHT: enhanced heat transfer). It was found that DHT can be restrained by decreasing the local heat flux in the entrance region. Superior local heat transfer performance is realized for cases with a nonuniform heat flux defined by a piecewise linear function. The present study provides fundamental insight into the mechanisms of heat transfer under a varying axial heat flux and shows the promise of adjusting the axial heat flux distribution to obtain NHT, or even EHT, for S-CO 2 flowing upward in a vertical tube.